2008
DOI: 10.1542/peds.2007-1308
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Profile of Sepsis in Neonates: Neutrophil CD64 as a Diagnostic Marker

Abstract: Neutrophil CD64 is a highly sensitive marker for neonatal sepsis. Prospective studies incorporating CD64 into a sepsis scoring system are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
130
4
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(147 citation statements)
references
References 49 publications
10
130
4
3
Order By: Relevance
“…16 In this study, neutrophil levels in saliva and blood from the case group were significantly higher than those of the control group. Similar to other neonatal sepsis studies, 17,18 we found significantly increased neutrophil levels in subjects at risk of sepsis, as evidenced by the elevation of neutrophil CD64, a very sensitive marker. bhandari et al reported that the combination of CD64 with an absolute neutrophil amount had a high negative predictive value (93%) and sensitivity (95%) for sepsis markers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…16 In this study, neutrophil levels in saliva and blood from the case group were significantly higher than those of the control group. Similar to other neonatal sepsis studies, 17,18 we found significantly increased neutrophil levels in subjects at risk of sepsis, as evidenced by the elevation of neutrophil CD64, a very sensitive marker. bhandari et al reported that the combination of CD64 with an absolute neutrophil amount had a high negative predictive value (93%) and sensitivity (95%) for sepsis markers.…”
Section: Discussionsupporting
confidence: 90%
“…bhandari et al reported that the combination of CD64 with an absolute neutrophil amount had a high negative predictive value (93%) and sensitivity (95%) for sepsis markers. 18 There have been several reports on TLR2 and TLR4 expression in newborn babies. Vieman et al conducted a TLR2 and TLR4 expression study on granulocytes and monocytes from the peripheral veins of 20 healthy adults and from the umbilical cord veins of 85 newborns (32 septic infants and 53 healthy infants).…”
Section: Discussionmentioning
confidence: 99%
“…A cut point of 3.62 had a sensitivity of 75%, specificity of 77% and a negative predictive value of 96%. 48 Index values below the cut points could be used to support the discontinuation of antimicrobials. Advantages of this assay include the requirement for only 50 μL of blood and availability of results within hours of the specimen being obtained.…”
Section: Neutrophil Markersmentioning
confidence: 99%
“…Furthermore, several studies have indicated that quantitation of the neutrophil CD64 is a worthwhile candidate for evaluation as a more sensitive and specific indicator of sepsis than the other available diagnostics tests (7) , that has high diagnostic specificity and sensitivity of neonatal sepsis (8,9) .…”
Section: Introductionmentioning
confidence: 99%